FILSAFAT PENDIDIKAN MATEMATIKA (MATEMATIKA SEBAGAI ALAT PIKIR DAN BAHASA ILMU) - Prima Mytra; Andi Kaharuddin; Fatimah Fatimah; Fitriani Fitriani (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2023)
The purpose of this study is to determine the history of mathematics, the role of mathematics as a tool of thought, and the role of mathematics as the language of science so that it can be useful for students and lecturers of Mathematics Education to know the history and role of mathematics as a tool of thought and language in everyday life. This type of research is descriptive research with a literature review approach by combining various references to articles, books and websites. The data used is secondary data. The findings are that mathematics as the language of science is mathematics used to express ideas, thoughts, ideas, feelings, and as a tool for communicating and interacting by humans. Mathematics as a tool of thought is a tool used to symbolize algorithms, manipulate numbers, recognize and find patterns, symbols, tables, and graphs.Keywords: The role of mathematics; Mathematics as a tool of thought; mathematics as the language of science.